2016
DOI: 10.1093/mnras/stw1799
|View full text |Cite
|
Sign up to set email alerts
|

Neutron star crust cooling in KS 1731−260: the influence of accretion outburst variability on the crustal temperature evolution

Abstract: Using a theoretical model, we track the thermal evolution of a cooling neutron star crust after an accretion induced heating period with the goal of constraining the crustal parameters. We present for the first time a crust cooling model -NSCool -that takes into account detailed variability during the full outburst based on the observed light curve. We apply our model to KS 1731-260. The source was in outburst for ∼12 years during which it was observed to undergo variations on both long (years) and short (days… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
74
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 42 publications
(82 citation statements)
references
References 42 publications
7
74
1
Order By: Relevance
“…dStar gives the crust temperature profile at all times; thus we can study the temperature in the crust at the time of the superburst. As discussed in Ootes et al (2016), the accretion rate during the outburst varies and is significantly higher in the earlier part than at the end. The persistent flux before the superburst (taken from Kuulkers et al 2002) is about 1.66 times higher than the average mass accretion rate we assume.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…dStar gives the crust temperature profile at all times; thus we can study the temperature in the crust at the time of the superburst. As discussed in Ootes et al (2016), the accretion rate during the outburst varies and is significantly higher in the earlier part than at the end. The persistent flux before the superburst (taken from Kuulkers et al 2002) is about 1.66 times higher than the average mass accretion rate we assume.…”
Section: Discussionmentioning
confidence: 94%
“…However, a recent investigation by Ootes et al (2016) has shown that variations in the accretion rate throughout the outburst influence the cooling curve. Especially important are variations at the end of the outburst, which can strongly influence the early part of the cooling curve and hence have a significant impact on the implied amount of extra heating at shallow depths.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations